(untitled) (Journal of Human Sciences, 2026)
This paper focuses on salt in Libyan during the Middle Ages, by shedding light on two main aspects: the first: monitoring the sites of the salt pans and the stages of the production process, and the characteristics of the salt product in the marshes of the Libyan lands. The second aspect: It deals with the process of exporting salt via land routes heading south to Africa beyond the Sahara, and this was affected by local and regional conditions, based on the information contained in the books of geographers and travelers, in addition to the writings of historians, to form a picture of the level of trade exchange between the Libyan countries and the countries of Sudan in particular, to understand in a deeper and more comprehensive way the impact of European economic penetration - which became clear with the second half of the eighth century AH / fourteenth century AD - on the freedom of commercial movement in the Islamic Maghreb in general and the Closer Maghreb in particular. The opinions presented in this paper are based on geographical and natural data presented in travel and geography books during the medieval period of history, as well as on recent studies that contributed to understanding the importance of salt in the international trade movement and its impact on the course of political events in the Mediterranean basin region, and on the trade of the cities of the Islamic Maghreb with the countries of sub-Saharan Africa. It is as it was said in the past: “Man can live without gold, but cannot live without salt.”